Altered functional connectivity of the default mode network in Williams syndrome: a multimodal approach. Issue 4 (July 2016) - Sampaio, Adriana; Moreira, Pedro Silva; Osório, Ana; Magalhães, Ricardo; Vasconcelos, Cristiana; Férnandez, Montse; Carracedo, Angel; Alegria, Joana; Gonçalves, Óscar F.; Soares, José Miguel
Abstract: Resting state brain networks are implicated in a variety of relevant brain functions. Importantly, abnormal patterns of functional connectivity (FC) have been reported in several neurodevelopmental disorders. In particular, the Default Mode Network (DMN) has been found to be associated with social cognition. We hypothesize that the DMN may be altered in Williams syndrome (WS), a neurodevelopmental genetic disorder characterized by an unique cognitive and behavioral phenotype. In this study, we assessed the architecture of the DMN using fMRI in WS patients and typically developing matched controls (sex and age) in terms of FC and volumetry of the DMN. Moreover, we complemented the analysis with a functional connectome approach. After excluding participants due to movement artifacts ( n = 3), seven participants with WS and their respective matched controls were included in the analyses. A decreased FC between the DMN regions was observed in the WS group when compared with the typically developing group. Specifically, we found a decreased FC in a posterior hub of the DMN including the precuneus, calcarine and the posterior cingulate of the left hemisphere. The functional connectome approach showed a focalized and global increased FC connectome in the WS group. The reduced FC of the posterior hub of the DMN in the WS group is consistent with immaturity of the brain FC patterns and may be associated with the singularity of their visual spatial phenotype. Abstract : Abnormal patterns of functional connectivity have been reported in several neurodevelopmental disorders. In this study we investigated the architecture of the Default Mode Network (DMN) and the global connectome using resting‐state fMRI in a group of individuals with Williams syndrome and in typically developing matched group. A decreased FC between the DMN regions and a global and inter‐hemispheric FC connectome increase was observed in the WS group. Moreover, the reduced FC of the posterior hub of the DMN in WS group is consistent with immaturity of the brain FC patterns and may be associated with the singularity of their visual spatial phenotype.